ANALISIS TINDAK TUTUR EKSPRESIF RADIO PRAMBORS PROGRAM SAPA MANTAN - Nadila Tasya Paramita; Asep Purwo Yudi Utomo (Universitas Sarjanawiyata Tamansiswa, 2020)
By acting speech we can know what response is later expressed by the reviewer through direct or indirect contact. An indirect example of one is visible when radio broadcasters make contact with listeners through the phone. One of the private radio in Indonesia that is very popular by the listener (kawula muda) has a program that contains the former segment Sapa. This research has a purpose to demonstrate the follow-up speech in the former Sapaprogram. In this analysis , the results stated that the expressive follow-up showed an expressive form between listeners and hearers then radio broadcasters as mediums in the radio prambors.